FAKTOR INDEKS HARGA PADA NILAI TUKAR PETANI DI PROVINSI SULAWESI UTARA - Tirsa E. Mumu; Charles R. Ngangi; Mex L. Sondakh; Jean F.J. Timban (COCOS, 2015)
ABSTRACTThis study aims to determine the problems that occur on the Farmers Exchange (NTP) in North Sulawesi Province from 2004 period until 2013. Data analysis used in this study is NTP. Based on the results, it can be concluded that the Farmers Exchange in 2004-2013 to move between 98.21 to 163.10 with an average of 122.89. In general,regional of North Sulawesi province has experience well-being, although in 2013 has a decline NTP, which is only 98.21. This is caused by the low value of agricultural production sold by farmers